Deglaciation of Fennoscandia. (1st September 2016) - Stroeven, Arjen P.; Hättestrand, Clas; Kleman, Johan; Heyman, Jakob; Fabel, Derek; Fredin, Ola; Goodfellow, Bradley W.; Harbor, Jonathan M.; Jansen, John D.; Olsen, Lars; Caffee, Marc W.; Fink, David; et al.
Abstract: To provide a new reconstruction of the deglaciation of the Fennoscandian Ice Sheet, in the form of calendar-year time-slices, which are particularly useful for ice sheet modelling, we have compiled and synthesized published geomorphological data for eskers, ice-marginal formations, lineations, marginal meltwater channels, striae, ice-dammed lakes, and geochronological data from radiocarbon, varve, optically-stimulated luminescence, and cosmogenic nuclide dating. This is summarized as a deglaciation map of the Fennoscandian Ice Sheet with isochrons marking every 1000 years between 22 and 13 cal kyr BP and every hundred years between 11.6 and final ice decay after 9.7 cal kyr BP. Deglaciation patterns vary across the Fennoscandian Ice Sheet domain, reflecting differences in climatic and geomorphic settings as well as ice sheet basal thermal conditions and terrestrial versus marine margins. For example, the ice sheet margin in the high-precipitation coastal setting of the western sector responded sensitively to climatic variations leaving a detailed record of prominent moraines and other ice-marginal deposits in many fjords and coastal valleys. Retreat rates across the southern sector differed between slow retreat of the terrestrial margin in western and southern Sweden and rapid retreat of the calving ice margin in the Baltic Basin. Our reconstruction is consistent with much of the published research. However, the synthesis of a large amount of existing and new data support refined reconstructions in some areas. For example, the LGM extent of the ice sheet in northwestern Russia was located far east and it occurred at a later time than the rest of the ice sheet, at around 17–15 cal kyr BP. We also propose a slightly different chronology of moraine formation over southern Sweden based on improved correlations of moraine segments using new LiDAR data and tying the timing of moraine formation to Greenland ice core cold stages. Retreat rates vary by as much as an order of magnitude in different sectors of the ice sheet, with the lowest rates on the high-elevation and maritime Norwegian margin. Retreat rates compared to the climatic information provided by the Greenland ice core record show a general correspondence between retreat rate and climatic forcing, although a close match between retreat rate and climate is unlikely because of other controls, such as topography and marine versus terrestrial margins. Overall, the time slice reconstructions of Fennoscandian Ice Sheet deglaciation from 22 to 9.7 cal kyr BP provide an important dataset for understanding the contexts that underpin spatial and temporal patterns in retreat of the Fennoscandian Ice Sheet, and are an important resource for testing and refining ice sheet models. Graphical abstract: Highlights: Compilation of geomorphological data; First esker map for Fennoscandian Ice Sheet. Compilation of geochronological data; 794 CN, 335 14 C, and 138 OSL dates. Deglaciation map Fennoscandian Ice Sheet; 22–13 (1 kyr) and 11.6–9.7 (0.1 kyr).